On Transnational and International History. - Chamberlin, Paul Thomas; Corinealdi, Kaysha; Ewing, Cindy; Fancy, Hussein; Ghosh, Arunabh; Herman, Rebecca; Jimenez, Raevin; John, Maria; Khalili, Laleh; Stephens, Julia; Scott, Erik R.; Slobodian, Quinn (American Historical Review, 2023)
A forum is presented on the topic of transnational history, with essays from twelve scholars including Quinn Slobodian, Professor of the History of Ideas at Wellesley College, Hussein Fancy, Associate Professor of History as Yale University and Rebecca Herman, Assistant Professor of History at the University of California, Berkeley. [EPC]